The Role of Philosophical Values in the Lontong Cap Go Meh Celebration in Fantasy Novel Writing - Shienny Megawati Sutanto (ARCHive-SR)
This research explores the potential of fantasy fiction to reintroduce Chinese-Indonesian youths to their cultural heritage, specifically focusing on the philosophical significance of Lontong Cap Go Meh, a traditional dish associated with the Cap Go Meh celebration. Through a qualitative study combining observation, interviews, and documentary analysis, this research identifies core philosophical values embedded in Lontong Cap Go Meh and examines how these values can be integrated into a fantasy narrative. Utilizing the Ethnic Food Identity theory, the study analyzes how Lontong Cap Go Meh embodies core philosophical values within the Chinese-Indonesian tradition. Visual Picture of the Story and Structural-Affect Theory of Stories are then applied to examine how these values can be effectively incorporated into the narrative structure of a fantasy novel. A prototype fantasy fiction novel was created and tested with target readers to assess its effectiveness in fostering cultural understanding and appreciation. The study found that Lontong Cap Go Meh is rich in philosophical values, including hope for prosperity, respect for tradition, and integration into Indonesian culture. These values were successfully integrated into the fantasy novel's narrative through plot, theme, character development, and the core message. User testing revealed a positive impact on target readers' understanding and appreciation of Chinese-Indonesian culture. This research offers valuable insights for creators seeking to use fantasy fiction to bridge cultural gaps and promote cultural understanding. It emphasizes the importance of accurately portraying cultural essence while crafting engaging narratives that resonate with young readers.